The Results of the Study of the Compactions of the Bottom of the Furrow in Plowing by Plug Corpusies as well as Tractor Wheels (Texas Journal of Agriculture and Biological Sciences, 2022)
In this article, the physical and mechanical properties of the soil during plowing, that is, hardness, density, In order to study the humidity, the results of the researches are presented